2022
DOI: 10.1001/jamaneurol.2022.3651
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing to Inform Epilepsy Treatment Management From an International Study of Clinical Practice

Abstract: ImportanceIt is currently unknown how often and in which ways a genetic diagnosis given to a patient with epilepsy is associated with clinical management and outcomes.ObjectiveTo evaluate how genetic diagnoses in patients with epilepsy are associated with clinical management and outcomes.Design, Setting, and ParticipantsThis was a retrospective cross-sectional study of patients referred for multigene panel testing between March 18, 2016, and August 3, 2020, with outcomes reported between May and November 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…A recent study found that genetic diagnoses in patients with epilepsy was associated with changes in clinical management in 49.8% of individuals and usually (81.7% of the time) within 3 months of receiving the result. 2 Thus early MEP testing may have implications for prompt changes to clinical care, including implementation of targeted treatment strategies. 3 Non-diagnostic metabolic testing and invasive procedures occurred more frequently in those individuals who underwent late compared with early genetic testing after clinical epilepsy diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that genetic diagnoses in patients with epilepsy was associated with changes in clinical management in 49.8% of individuals and usually (81.7% of the time) within 3 months of receiving the result. 2 Thus early MEP testing may have implications for prompt changes to clinical care, including implementation of targeted treatment strategies. 3 Non-diagnostic metabolic testing and invasive procedures occurred more frequently in those individuals who underwent late compared with early genetic testing after clinical epilepsy diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…We were also limited in our interpretation by lack of parental data for some patients, but we chose to include all individuals regardless of parental availability. Furthermore, as with a recent study reporting clinical utility of epilepsy panels, our EMR-based assessment could not accurately determine impact on hospitalization rates, morbidity or mortality, clinical trials eligibility, and avoidance of testing procedures (such as lumbar puncture, magnetic resonance imaging, or electroencephalography).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic ndings will provide valuable insight into the natural history of epilepsy heterogeneity. Most recently, the awareness of the impact of genetic background on developing drug-resistant epilepsy has gradually increased, and new genetic techniques are proving very useful in clinical practice and may help clinicians to explain the clinical presentation of drug-resistant epilepsy [13]. In addition, this will likely help us understand the impact of personalized and precise pharmacological treatment on epilepsy [14].…”
Section: Discussionmentioning
confidence: 99%